ТРУДНОСТИ ДИФФЕРЕНЦИАЛЬНОЙ ДИАГНОСТИКИ НЕСПЕЦИФИЧЕСКОГО ЯЗВЕННОГО КОЛИТА И БОЛЕЗНИ КРОНА В КЛИНИЧЕСКОЙ ПРАКТИКЕ. СОБСТВЕННОЕ НАБЛЮДЕНИЕ - Н. С. Хрулёва; Н. Н. Боровков (SINAPS LLC, 2013)
The all-Russian frequency data of ulcerative colitis and Crohn's disease are resulted in the article, the case report reflecting the difficulties of differential diagnostics of ulcerative colitis and Crohn's disease is presented.